Chemoradiotherapy versus radiotherapy alone in elderly patients with stage III non-small cell lung cancer: A systematic review and meta-analysis. (September 2016) - Dawe, David E.; Christiansen, David; Swaminath, Anand; Ellis, Peter M.; Rothney, Janet; Rabbani, Rasheda; Abou-Setta, Ahmed M.; Zarychanski, Ryan; Mahmud, Salaheddin M.
Highlights: Elderly (≥70 years) stage III NSCLC patients are often excluded from standard CRT. Our meta-analysis shows CRT is superior to RT (HR 0.66) in patients ≥70 years. Non-hematological toxicity does not differ between CRT and RT. Neutropenia and thrombocytopenia are more common with CRT. CRT is a reasonable standard of care for fit stage III NSCLC patients ≥70 years old. Abstract: In stage III non-small cell lung cancer (NSCLC), the standard of care in young patients is chemoradiotherapy, but this standard is not as clearly established for older patients. We aimed to determine the efficacy and harm associated with chemoradiotherapy versus radiotherapy alone in elderly (≥70 years), stage III NSCLC patients through a systematic review. We conducted a systematic search of MEDLINE, EMBASE, CENTRAL, Scopus, Web of Science and conference proceedings. Two reviewers independently identified randomized trials (RCT) and extracted trial-level data. Risk of bias was assessed and meta-analysis was conducted looking at survival and safety outcomes. We included three trials and subgroup data from one systematic review. The three RCTs had high risk of bias due primarily to lack of blinding and the systematic review scored 4/11 using the AMSTAR tool. Overall survival (HR 0.66, 95% CI 0.53–0.82; I2 0%; 3 trials; 407 patients) and progression-free survival (HR 0.67, 95% CI 0.53–0.85; I2 0%; 2 trials; 327 patients) both favored chemoradiotherapy. Risk of treatment-related death and grade 3+ pneumonitis were not significantly different between groups. In conclusion, treatment of stage III NSCLC patients 70 years or older with chemotherapy and radiotherapy is associated with improved overall survival compared to radiotherapy alone. With the exception of increased hematological toxicity, CRT appears to be tolerable in fit elderly patients and represents a reasonable standard of clinical care.